Childhood obesity: implications for current and future health - Katzmarzyk, Peter T. (Henry Stewart Talks, 2024)
Identifying overweight and obesity in children, Factors associated with childhood obesity, Obesity and health in childhood, Childhood obesity and future health, Clinical resources, Obesity in childhood is related to obesity in adulthood, Elevated CVD risk factors, Premature mortality in adulthood